Long-term outcomes of a novel method of femoropopliteal bypass - A. B. Zakeryaev; R. А. Vinogradov; P. V. Sukhoruchkin; S. R. Butaev; T. E. Bakhishev; A. I. Derbilov; E. R. Urakov; A. G. Baryshev; V. A. Porkhanov (Российский кардиологический журнал, 2022)
Aim. To analyze the long-term outcomes of a novel method of femoropopliteal bypass (FPB) surgery.Material and methods. This retrospective, open-label, comparative study for the period from October 1, 2016 to December 25, 2019 at the Research Institute of the S. V. Ochapovsky Regional Clinical Hospital №1 (Krasnodar Krai) included 473 patient who underwent FBP. Depending on the type of graft, 5 groups were formed: group 1 (n=266) — reversed vein (great saphenous vein (GSV)); group 2 (n=59) — autologous vein graft (GSV) prepared in situ; group 3 (n=66) — autologous vein graft (GSV) prepared ex situ; group 4 (n=9) — synthetic graft (Jotec, Germany); group 5 (n=73) — upper limb veins. In all cases, Multislice computed tomography angiography revealed an extended (25 cm or more) Trans-Atlantic Inter-Society Consensus (TASC II) class D occlusion of the superficial femoral artery. The longterm follow-up period was 16,6±10,3 months. The technical result of novel FPB technique was achieved using proposed type of an autologous vein graft preparation, in which, after GSV isolation, ex situ valvulotomy was performed, followed by the non-reversed subfascial orthotopic graft passage along the neurovascular bundle by tunneling (Sheath Tunneler Set; Peripheral Vascular, USA) soft tissues. The GSV ex situ was prepared as follows: the GSV was isolated from the saphenofemoral fistula in the distal direction to the required length and removed from the wound. Further, valvulotomy was performed through the proximal end of GSV. Then the valvulotome was removed and a metal cannula was inserted. Through it, a saline solution at indoor temperature with unfractionated heparin was injected into the GSV lumen, simulating blood flow, and the quality of the performed valvulotomy was assessed.Results. In the inhospital postoperative period, all complications developed in groups 1, 2, 3 and 5. However, no significant intergroup statistical differences were found. In the long-term follow-up, there were no significant intergroup differences in the prevalence of deaths (group 1: 4,6%; group 2: 1,7%; group 3: 4,6%; group 4: 0%; group 5: 2,8%; p=0,78), myocardial infarction (group 1: 1,9%; group 2: 0%; group 3: 1,5%; group 4: 0%; group 5: 0%; p=0,62), ischemic stroke (group 1: 0,8%; group 2: 1,7%; group 3: 1,5%; group 4: 0%; group 5: 0%; p=0,8) and shunt thrombosis (group 1: 14,5%; group 2: 19,3%; group 3: 18,5%; group 4: 44,4%; group 5: 19,7%; p=0,16). However, the highest number of limb amputations (group 1: 4,2%; group 2: 5,3%; group 3: 9,2%; group 4: 22,2%; group 5: 1,4%; p=0,03) and the highest rate of composite endpoint (sum of all complications) (group 1: 26,0%; group 2: 28,1%; group 3: 35,4%; group 4: 66,7%; group 5: 23 ,9%; p=0,05) were observed in patients with synthetic prosthesis.Conclusion. FPB with the autologous vein graft ex situ is characterized by a comparable inhospital and long-term outcomes with BPS using the reversed autologous vein and autologous vein in situ. Thus, this surgical technique may become one of the preferable operations for patients with extended occlusion of the superficial femoral artery.